28-Day Repeated Dose Oral Toxicity of a Herbal Mixture Dia-2, Containing Standardized Extracts of Allium Sativum and Lagerstroemia Speciosa In Sprague Dawley Rats - KS. Kesavanarayanan; P. Kalaivani; G.Ramakrishnan; S.Sathiya; V.Ranju; R.Jyothipriya; Chinnasamy Selvakkumar; C.Saravanababu; J.venkhatesh; R.Ilavarasa; S.Kavimani; D Prathiba (International Journal of Phytomedicine, 2012)
Allium sativum [ASE] and Lagerstroemia speciosa [LSE] are widely used in folk medicine as a medication for diabetes. DIA-2 is a polyherbal antidiabetic formulation containing fixed combination [1:1 w/w] of standardized aqueous extracts of Allium sativum bulbs containing 1.1 % alliin w/w and 40 % hydroalcholic extract of Lagerstroemia speciosa leaves containing 1.28% w/w corosolic acid. Earlier studies in our laboratories have demonstrated the oral safety of DIA-2 on acute oral exposure to female Sprague Dawley [SD] rats and the antidiabetic activity of DIA-2 in high-fat diet fed/streptozotocin-induced diabetic rats. The ingredients of DIA-2 have long history safety but however, there is little toxicological information regarding the oral safety on repeated exposure of ASE and LSE when given as a combined mixture. The present study evaluated the repeated oral toxicity of DIA-2 in both the sexes of SD rats. Rats were treated orally once with 62.5, 125, 250 mg/kg body weight, and animals were observed till the 28 days of study. On repeated oral administration, DIA-2 showed did not exhibit any clinical signs of toxicity, mortality, significant change in food, water consumption, body weight, mortality, clinical chemistry, hematology, organ weight, gross pathology and histopathology when varying doses of the DIA-2 were administered orally once daily for a period of 28 days. The NOAEL [No Observed Adverse Effect Level] of DIA-2 in this study was identified to be greater than 250 mg/kg/day. The results from the study suggest that there are no toxicologically significant effects on 28 day repeated oral administration of DIA-2 and the data also provide satisfactory preclinical evidence on its oral safety to support its use as a therapeutic agent in the treatment of diabetes mellitus.